2016
DOI: 10.1038/srep35491
|View full text |Cite
|
Sign up to set email alerts
|

Both the anti- and pro-apoptotic functions of villin regulate cell turnover and intestinal homeostasis

Abstract: In the small intestine, epithelial cells are derived from stem cells in the crypts, migrate up the villus as they differentiate and are ultimately shed from the villus tips. This process of proliferation and shedding is tightly regulated to maintain the intestinal architecture and tissue homeostasis. Apoptosis regulates both the number of stem cells in the crypts as well as the sloughing of cells from the villus tips. Previously, we have shown that villin, an epithelial cell-specific actin-binding protein func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…Slender cells, with a strong eosinophilic cytoplasm, were observed only in the distal intestine, on the apical part of the complex folds and in the pyloric caeca. These features correspond to the early apoptotic stages in which dying cells assume the typical funnel-like structure with crescent nuclei and display a strongly acidophilic cytoplasm due to chromatin condensation [34].…”
Section: Discussionmentioning
confidence: 72%
“…Slender cells, with a strong eosinophilic cytoplasm, were observed only in the distal intestine, on the apical part of the complex folds and in the pyloric caeca. These features correspond to the early apoptotic stages in which dying cells assume the typical funnel-like structure with crescent nuclei and display a strongly acidophilic cytoplasm due to chromatin condensation [34].…”
Section: Discussionmentioning
confidence: 72%
“…S4 D , Right ) d after 56 Fe relative to control and γ-rays, suggesting increased cell–ECM attachment promoting reduced cellular mobility. Coordinated cell migration along the crypt–villus axis also requires timely cell extrusion in the villus tip area, and proapoptotic NH 2 -terminal villin has been reported to play key roles in cell shedding ( 18 ). Immunohistochemistry for NH 2 -terminal villin showed reduced expression in the villus tip area at 7 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Integrins have been reported to modulate the DNA damage response, and activation of β1-integrin decreased DNA damage-induced apoptosis ( 16 ). Migrating IECs are shed at the villus tip via apoptosis, and the actin-binding protein villin, through its differential cleavage and interaction with actin, has been shown to regulate cell turnover in the villi ( 18 ). While heavy-ion radiation is capable of inducing long-lasting cellular stress and DNA damage ( 4 , 19 ), its effects on key cellular processes involved in IEC migration and pathological implications of their dysregulation on GI tissue are poorly defined.…”
mentioning
confidence: 99%
“… 18 , 101 , 102 However, two aspects of villin’s regulation in the apoptosis of gastrointestinal epithelium have been reported, which include maintaining morphology and homeostasis. 103 These processes may also be responsible for chemoresistance in OS therapy, which has been proved in ovarian and head-and-neck cancers. 104 , 105 Meanwhile, in breast cancer, it has been indicated that fascin has the capability to enhance the resistance of chemotherapy and makes for a poor prognosis in patients.…”
Section: Abps and Oncotherapy In Osmentioning
confidence: 99%